How Fair Is Actuarial Fairness? - Landes, Xavier (Journal of business ethics, 2015)
Insurance is pervasive in many social settings. As a cooperative device based on risk pooling, it serves to attenuate the adverse consequences of various risks (health, unemployment, natural catastrophes and so forth) by offering policyholders coverage against the losses implied by adverse events in exchange for the payment of premiums. In the insurance industry, the concept of actuarial fairness serves to establish what could be adequate, fair premiums. Accordingly, premiums paid by policyholders should match as closely as possible their risk exposure (i.e. their expected losses). Such premiums are the product of the probabilities of losses and the expected losses. This article presents a discussion of the fairness of actuarial fairness through three steps: (1) defining the concept based on its formulation within the insurance industry; (2) determining in which sense it may be about fairness; and (3) raising some objections to the actual fairness of actuarial fairness. The necessity of a normative evaluation of actuarial fairness is justified by the influence of the concept on the current reforms of public insurance systems and the fact that it highlights the question of the repartition of the gains and burdens of social cooperation.